2019
DOI: 10.3348/kjr.2018.0424
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Magnetic Resonance Imaging Using Compressed Sensing for Intracranial and Extracranial Arteries: Comparison with Conventional Parallel Imaging

Abstract: Objective To compare conventional sensitivity encoding (SENSE) to compressed sensing plus SENSE (CS) for high-resolution magnetic resonance imaging (HR-MRI) of intracranial and extracranial arteries. Materials and Methods HR-MRI was performed in 14 healthy volunteers. Three-dimensional T1-weighted imaging (T1WI) and proton density-weighted imaging (PD) were acquired using CS or SENSE under the same total acceleration factors (AF t )-5.5, 6.8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
(27 reference statements)
3
20
0
Order By: Relevance
“…CS also provided robust and repeatable results with an acceleration factor of 1.5 (15). Further, CS with an acceleration factor of 3-5 applied to intracranial VW-MRIs yielded higher or comparable image quality to marked time reductions (13,14). Here, we used an extra reduction factor of 1.5 in VISTA-CS, which did not significantly affect image quality.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…CS also provided robust and repeatable results with an acceleration factor of 1.5 (15). Further, CS with an acceleration factor of 3-5 applied to intracranial VW-MRIs yielded higher or comparable image quality to marked time reductions (13,14). Here, we used an extra reduction factor of 1.5 in VISTA-CS, which did not significantly affect image quality.…”
Section: Discussionmentioning
confidence: 98%
“…Several prior studies reported that CS achieved substantial scan time reduction while providing similar or superior SNR, CNR, VW delineation, and image quality in intracranial VW-MRIs (13,14). Those studies enrolled mostly healthy volunteers; therefore, validation in large patient cohorts was necessary to use CS in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research was performed in accordance with relevant guidelines and regulations. The study population and image acquisitions were as previously described 9 .…”
Section: Methodsmentioning
confidence: 99%
“…However, loss of image quality, as compared with a fully sampled MRI, is unavoidable. A previous study 9 reported that CS HRPD MR images with high acceleration factors yields unacceptable imaging for radiological reading. As low-quality vessel wall imaging hampers accurate diagnosis 9 11 , improving the image quality of CS HRPD MR images would be beneficial for accurate radiological reading and diagnosis.…”
Section: Introductionmentioning
confidence: 99%